Comparative Efficacy of NAFLD Therapies and Biomarker Associations: A Meta-Analysis Based on Liver Fat Content - Haoxiang Zhu; Ling Xu; Yinhua Lv; Juan Yang; Jihan Huang; Qingshan Zheng; Guang Ji; Lujin Li (Gastro Hep Advances)
Background and Aims: This study aims to conduct a comprehensive quantitative analysis of various nonalcoholic fatty liver disease (NAFLD) therapeutics, utilizing magnetic resonance (MR)-detected liver fat content (LFC) as the efficacy endpoint, and to identify biomarkers correlated with changes in LFC based on published literature. Methods: We performed a systematic search of public databases for placebo-controlled randomized trials on NAFLD up to September 29, 2023. A random-effects meta-analysis was employed to assess efficacy differences between drugs with various mechanisms and placebo. Initial Pearson correlation analysis explored the relationships between biomarkers and LFC. For biomarkers showing significant correlations with LFC, further modeling analysis was conducted to examine their relationship characteristics. Results: Our analysis included 36 studies with 3222 subjects and 33 investigational drugs, which were categorized into 6 mechanistic groups. Drugs such as fibroblast growth factor agonists, and those targeting adipocytes, inflammation, or fibrosis, showed greater efficacy in reducing LFC compared to Resmetirom, which has an efficacy of reducing LFC by 5.2%. From the 121 biomarkers analyzed, alanine aminotransferase and aspartate aminotransferase demonstrated moderate correlations with LFC; specifically, changes of −5.9 U/L in alanine aminotransferase or −3.3 U/L in aspartate aminotransferase were associated with an additional 1% reduction in LFC. Conclusion: The results of this study provide valuable insights for the clinical development of future NAFLD therapeutics, highlighting the efficacy of specific drug mechanisms and the potential of certain biomarkers as surrogate endpoints.